MODEL BISNIS CANVAS HUTAN PINUS LIMPAKUWUS PURWOKERTO - Hermin Endratno; Ade Rusman; Arini Hidayah (Derivatif : Jurnal Manajemen, 2021)
Mapping the business model with the business model canvas approach, which is carried out on the nine block elements in it, which includes the customer segment, value proposition, channel, customer relationship, revenue stream, key activity, key resource, key partnership, and the cost structure are broadly said to be sufficient. good. The existing business model is able to fulfill the nine building block elements of the business model canvas. Based on the results of the evaluation using a SWOT analysis of the nine building block elements on the business model canvas regarding the strengths and weaknesses, opportunities, and threats of the Limpakuwus pine forest, it produces a strategic conclusion that can be used as a recommendation for the Limpakuwus pine forest management so that it can improve its business model. there is. Of the nine building block elements in the existing business model canvas, the researchers recommend that additions are aimed at several building blocks, namely value propositions, key partnerships and customer relationships.Keywords: Business Model Canvas, Forest Tourism